Applications of the pinhole effect in clinical vision science - Kanclerz, Piotr; Khoramnia, Ramin; Atchison, David (Journal of cataract and refractive surgery, 2024)
The pinhole effect is commonly used to discriminate uncorrected refractive error from ocular diseases. A small aperture limits the width of light beams entering the eye, thus increasing the depth of focus. The pinhole effect has also been used in spectacles, contact lenses, corneal inlays, and intraocular lenses (IOLs) to improve reading by compensating for loss of accommodative function. Pinhole spectacles improve near visual acuity, but reduce reading speed, increase interblink interval, and decrease tear break-up time. For contact lenses and IOLs, pinhole devices are usually used in the nondominant eye, which allow compensation of various refractive errors and decrease spectacle dependence. Pinhole corneal inlays are implanted during laser in situ keratomileusis or as a separate procedure. Pinhole IOLs are gaining popularity, particularly as they do not bring a risk of a local inflammatory reaction as corneal inlays do. Disadvantages of using the pinhole effect include high susceptibility to decentration, decrease in retinal luminance levels, and difficulties in performing fundus examinations or surgery in eyes with implanted devices. There are also concerns regarding perceptive issues with different retinal illuminances in the 2 eyes (the Pulfrich effect).